Childhood victimization and poly-victimization of online sexual offenders: A developmental psychopathology perspective. (July 2022) - Chopin, Julien; Fortin, Francis; Paquette, Sarah
Abstract: Background: Research on childhood victimization of individuals involved in online sexual offending during adulthood is scarce. Studies focusing on adverse childhood of individuals involved in offline child abuse suggested that childhood trauma was associated with an increased probability of sexual offending during adulthood. Objective: The purpose of this study is to explore the role that childhood victimization may have in the development of risk factors that increase the likelihood of being involved in online sexual offending. Participants: This comparative study analyzed the characteristics of 127 individuals involved in online sexual offending who did not experience childhood victimization and 77 individuals involved in online sexual offending who experienced childhood victimization. Methods: Bivariate and regression analyses were conducted to identify variables associated with the presence of victimization and polyvictimization during childhood. Next, structural equation modeling analysis was used to identify the direct and indirect relationships between childhood (poly)victimization and the development of risk factors. Results: Results showed that individuals who experienced childhood victimization presented different risk factors and cognitions compared to those who did not. Depending on the type of victimization experienced, criminogenic cognitions, antisocial behaviors, and sexual interests for children were more likely to be developed. Conclusions: For individuals involved in online sexual offending during adulthood, childhood abuse is directly associated with the development of offense-supportive cognitions, substance abuse, and youth engagement in sexual offending, while sexual interests for children and sense of loneliness are indirect consequences of childhood trauma.